Estimation of electron temperature in atmospheric pressure dielectric barrier discharge using line intensity ratio method - Shrestha, R; Tyata, RB; Subedi, DP (Kathmandu University Journal of Science, Engineering and Technology, 2013)
Dielectric Barrier Discharge was produced by applying high voltage AC source of frequency (10-30 KHz) and potential difference of (0-20) kV across two parallel plate electrodes with glass as dielectric barrier. Optical emission spectroscopy was used for the characterization of the discharge produced at atmospheric pressure. The emission spectra in the range of 200 nm to 850 nm have been analyzed to estimate the electron temperature by line intensity ratio method. The results showed that the electron temperature is about 0.9 eV. Kathmandu University Journal of Science, Engineering and Technology Vol. 8, No. II, December, 2012, 37-42 DOI: http://dx.doi.org/10.3126/kuset.v8i2.7323